STUDI PERSEPSI IBU TENTANG SIRKUMSISI (SUNAT) PADA PEREMPUAN DI DESA TANGGUNGPRIGEL KECAMATAN GLAGAH KABUPATEN LAMONGAN - Tintin Hariyani; Izzatul Mukhlisoh (STIKES dan AKZI Karya Husada Kediri, 2022)
Female circumcision is the act of removing the tip of the clitoral hood or the labia minora and Majora. Female circumcision in Indonesia is generally based on community customs and beliefs. The study aimed to examine how mothers perceive the circumcision of girls in the village of Prigel in Lamongan Her Regency, Glagar District. The study design uses descriptive methods with qualitative data. The variable in this study was maternal perceptions of female circumcision. The study was conducted on 40 mothers with daughters aged 0-5 years and used a targeted sampling technique to obtain a sample of 36 respondents. The tool used in this study is a questionnaire. The data obtained were analyzed in percentage form. We found that 24 respondents (67%) had very high awareness and 12 respondents (33%) had high awareness. The number of mothers whose daughters were uncircumcised was 22 respondents (61%), and the number of mothers whose children had female circumcision was 14 respondents (39%). The practice of female circumcision is usually performed on children aged 0 days to 5 years and even older. It is still practiced because it is affected by religious and cultural factors so mothers cannot refuse and ask their children to practice female circumcision. is very dangerous to the reproductive health of girls, as it can cause infections and disease disorders and can cause sexual problems as adults.